The Rise of Young Enterpreneurial Farmers in Banten, Indonesia - Abdul Hamid; Bayu Nurrohman; M Dian Hikmawan; Ramadhan, Gilang; Mayrudin, Yeby Ma’asan (International Journal of Psychosocial Rehabilitation, 2020)
This research aims to understand the development of entrepreneurship among young generation farmers in Banten, Indonesia when they faced deactivation. It used a qualitative approach with descriptive methods. The finding was the emerge of new farmer generation who met the criteria as agricultural entrepreneurs, namely Jawara Farm and Selaras Farm. They moved from peasant agriculture – which is a household-based business – to entrepreneurial agriculture. They made farming activities as a well-managed business to get profits and grow the business independently. Problems they faced were the lack and incompatibility of government assistances as well as the difficulty of capital access. Based on the findings, this research recommended that the government role could facilitate the growth of agricultural entrepreneurs through the right assessment, especially in funding and business assistance.